Students’ Perspectives on The Use of Picture Strategy in Learning Descriptive Text at SMA Santo Petrus Medan: Penelitian - Eska Agustinus Sihotang; Fiber Yun Almanda Ginting; Junita Siahaan; Meikardo Samuel Prayuda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research investigates students’ perspectives on the use of picture strategy in learning descriptive texts at SMA Santo Petrus Medan, Medan. The study employed a descriptive qualitative design, involving 34 students from class XI-B as the participants. Data were collected through semi-structured interviews and questionnaires to explore students’ perceptions, experiences, and attitudes toward the use of pictures as learning media. The purpose of this study was to identify the benefits of picture strategy in enhancing students’ understanding and creativity in writing descriptive texts and to determine how students perceive its effectiveness in their learning process. The cognitive domain showed the highest percentage (62.50%), indicating that pictures effectively supported students’ comprehension, imagination, and vocabulary enrichment. The affective domain (20.83%) reflected an increase in students’ motivation, confidence, and interest in learning. Students stated that pictures made learning “more fun, less boring,” and helped them to express ideas with greater enthusiasm. The psychomotor domain (16.67%) demonstrated improvement in students’ writing performance, particularly in organizing ideas and maintaining coherence in their descriptive texts. In conclusion, the picture strategy proved to be an effective and motivating pedagogical tool that enhanced students’ cognitive understanding, emotional engagement, and technical writing skills in descriptive text learning